DESIGN PATTERNS OF WOMEN EMPOWERING MSMEs THROUGH FINANCIAL MANAGEMENT PLANNING AND REPORTING AND UTILIZATION OF INFORMATION TECHNOLOGY - Rosyid Nur Anggara Putra; Muh. Rudi Nugroho; Alif Khuwarizmi Maulana Julendra; Alif Miftahul Fahmi (Journal of Islamic Economy and Community Engagement, 2022)
This study aims to develop a training pattern design to improve the ability of MSME actors in running their businesses. The first is to design financial planning and reporting in Patukgawemulyo Village, Mirit District, Kebumen Regency; Identify priorities for developing MSME actors in Patukgawemulyo Village, Mirit District, Kebumen Regency in fulfilling the family economy. Formulating a training pattern for female MSME actors in planning and compiling financial reports in Patukgawemulyo Village, Mirit District, Kebumen Regency. The implementation of this research uses the participatory action research (PAR) method, while the pattern is that the planning and financial reporting of MSME actors in Patukgawemulyo Village, Mirit District, Kebumen Regency is still done manually and mixes personal needs with business, so it is difficult to know the real condition of the business whether it is profitable or not. loss, the priority of developing MSME actors in Patukgawemulyo Village, Mirit District, Kebumen Regency based on the analysis is that administrative arrangements are carried out both manually and using information technology; The pattern of training for MSME actors in planning and compiling financial reports in Patukgawemulyo Village, Mirit District, Kebumen Regency begins with basic accounting equations, and can also take advantage of information technology assistance in preparing financial reports.